A note on the EM algorithm for estimation in the destructive negative binomial cure rate model. Issue 12 (13th August 2017) - Gallardo, Diego I.; Gómez, Yolanda M.; de Castro, Mário
ABSTRACT: In this note we present a modification in the EM algorithm for the destructive negative binomial cure rate model. This alteration enables us to obtain the estimates of the whole parameter vector from the complete log-likelihood function, avoiding the corresponding observed log-likelihood function, which is more involved. To achieve this goal, we resort to the mixture representation of the negative binomial distribution in terms of the Poisson and gamma distributions.